Studies of thermonuclear neutron usage means for radioactive waste transmutation - Rudychev, Y.V.; Slabospitskiy, R.P.; Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2008)
Two variants of radwastes transmutation schemes using thermonuclear neutrons are considered. In the first case transuranium elements and fission products are not separated while in the second case these are irradiated separately. Advantages and drawbacks of both cases were analyzed. Simulation of radwastes transmutation systems was performed. Analysis of radwastes transmutation efficiency for all cases was carried out. Physical backgrounds for radwaste transmutation by thermonuclear neutrons were prepared. Рассматривается два варианта системы трансмутации радиоактивных отходов (РАО) с помощью термоядерных нейтронов. В одном – трансурановые элементы и продукты деления не отделены друг от друга, в другом варианте – облучаются раздельно. Проанализированы преимущества и недостатки каждого из вариантов. Выполнено моделирование систем трансмутации РАО. Проанализирована эффективность трансмутации РАО для каждого из вариантов. Подготовлено физическое обоснование для трансмутации РАО термоядерными нейтронами. Розглядається два варіанти системи трансмутації радіоактивних відходів (РАВ) за допомогою термоядерних нейтронів. В одному – трансуранові елементи і продукти ділення не відокремлені один від одного, в іншому варіанті – опромінюються роздільно. Проаналізовано переваги і недоліки кожного з варіантів. Виконано моделювання систем трансмутації РАВ. Проаналізовано ефективність трансмутації РАВ для кожного з варіантів. Підготовлено фізичне обґрунтування для трансмутації РАО термоядерними нейтронами.